Tradisi Qunutan di Pertengahan Ramadhan: (Studi Living Hadis di Kecamatan Kasemen, Kota Serang, Banten) - Muchlas Hakho Bahri; Halawatul Kamala; Siti Yulinda Nurhalimah; Lia Aprilia; Gendis Ayu Wulan Maharani; Salsabila Itsnaini (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
The aim of this research is to get a clear picture of the meaning of each tradition that is still carried out by the Al-Ikhlas prayer room in Kasemen until now. The explanation of this research is to describe the meaning and motive for implementing Qunutan in the Al-ikhlas prayer room. This research uses functional structure research methods. The results of this research show the meaning of the Qunutan tradition in the Al Ikhlas prayer room, namely as a very special form of time to pray and ask for forgiveness and blessings from Allah SWT. Qunut in the month of Ramadan is usually related to prayers performed on the night of Lailatul Qadar, one of the most special nights in the month of Ramadan, as it involves participation in joint religious activities such as evening prayers, reading the Koran, and praying. Many people also do good deeds, such as giving alms or doing good to others, and guidance from Allah. During the last 10 nights of Ramadan, especially in searching for Laylatul Qadar, the Kasemen people often strengthen the practice of qunut as part of their intensive worship. The practice of qunut in the month of Ramadan is an important part of Muslims’ efforts to get closer to Allah and obtain blessings in the holy month of Ramadan which is considered full of grace.